Late Quaternary relative humidity changes from Mt. Kilimanjaro, based on a coupled 2H-18O biomarker paleohygrometer approach - Hepp, Johannes; Greule, Markus; Keppler, Frank (Quaternary international, 2017)
Our understanding of African paleoclimate/hydrological history is mainly based on lake level and lake sediment studies. It improved during the last decade thanks to emerging stable isotope techniques such as compound-specific deuterium analysis of sedimentary leaf wax biomarkers (δ2Hleaf-wax). Here we present the results from a multi-proxy biomarker study carried out on a ∼100 ka loess-like paleosol sequence preserved in the Maundi crater at ∼2780 m a.s.l. on the southeastern slopes of Mt. Kilimanjaro in equatorial East Africa. The Maundi stable isotope records established for hemicellulose-derived sugars, lignin- and pectin-derived methoxyl groups, leaf wax-derived fatty acid and n-alkane biomarkers (δ18Osugars, δ2Hmethoxyl groups, δ2Hfatty-acids and δ2Hn-alkanes, respectively) reveal similar patterns, but also some distinct differences are obvious. The periods from ∼70 to 60 ka, the Last Glacial Maximum (LGM) and the Younger Dryas (YD) are characterized by more positive δ values, whereas during the Holocene, and around 30, 39, and 56 ka BP more negative δ values are determined. The application of a ‘coupled δ2Hn-alkane-δ18Osugar paleohygrometer’ approach allows us to derive information about Late Quaternary changes of air relative humidity at the Maundi study site. Reconstructed changes of mean day-time relative humidity (RHD) are in good agreement with pollen results from the study area. Apart from the overall regional moisture availability, the intensification versus weakening of the trade wind inversion, which affects the diurnal montane atmospheric circulation on the slopes of Mt. Kilimanjaro, is suggested as a local factor which may contribute to the observed variability of RHD at Maundi study site. The combined usage of δ2Hn-alkanes and δ18Osugars allowed us to reconstruct δ2H/δ18O of source water utilized by plants in the study area, which is directly linked to local precipitation. The results of this reconstruction caution against a straightforward interpretation of δ2Hleaf-wax and δ18Osugars records as proxies for isotopic composition of local precipitation because variable and primarily RH-dependent isotopic evaporative enrichment of leaf water can mask changes of δ2Hprec/δ18Oprec in the past. The biomarker-based δ2H/δ18Osource-water records derived for the Maundi site revealed a discernible link with the reconstructed RHD record; lower RHD values were generally observed during periods characterized by more negative δ2H/δ18Osource-water values, indicating a reverse relationship with the expected precipitation amount. This indicates that the empirical relationship between amount of rainfall and its isotopic composition, observed nowadays on monthly timescale in the East African region, might not be valid on millennial time scale.
Gesehen am 20.02.2018
Im Titel sind die Zahlen 2 und 18 hochgestellt